Incidence of Low Clouds at Bombay airport (Santacruz) with reference to Jet landings with the help of the Instrument Landing System (ILS) - SIROMANI, P. (MAUSAM, 1966)
Santacruz airport constitutes a high traffic density area, with a- substantial number of jet aircraft movements. Aviation hazards at this airport get particularly accentuated during the monsoon season on account of the occurrence of very low clouds, strong gusty winds and poor visibility conditions in mist or haze, or showers. There are a- few important hill features a-round the airport, not far from the landing area. The airport is equipped with standard radio navigational aids, namely, very high frequency omnidirectional range (VOR), Instrument Landing System (ILS), the Aerodrome Surveillance Radar (ASR). A precision approach radar (PAR) will become operational at this airport shortly. On the ILS the glide path angle has recently been reduced from 4 degrees to 3.3 degrees above the horizon, necessitating the approach of the aircraft generally at a lower altitude, the altitude above the middle marker being of the order of 561 ft only. The distance of the middle marker from ARP is 2972 m (1.6 n.m.). Fig. 1 is the instrument approach chart for the Bombay airport. The aviation hazards that may be encountered by the jet aircraft especially in the monsoon season, on the phase of the final approach, have been discussed in this note with reference to climatological statistics and the synoptic climatology of this airport. It is hoped that the result arrived at will be of some practical value to pilots operating jet aircraft and to air traffic controllers.